A Semiotic analysis of the children's program HIRAYAMANAWARI - Colindres, Mary Rose M.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This analysis of Hirayamanawari focuses on how the children's program semiotically produces values through the fantasy genre. Fifteen episodes are included in this study. These episodes are individually analyzed using the framework of semiotics, which is the study of signification. Another framework used here is the fantasy theme analysis. This theory holds that a group's or a community's rhetorical vision is composed of the fantasy themes shared among its members. As used in this study, the fantasy themes refer to the ideas, themes and beliefs conveyed by the program. By determining such fantasy themes, this study identified the rhetorical visions held by Hirayamanawari. The researcher found out that contrary to the belief that the use of fantasy is merely an attemot to escape reality, the show utilizes this to create a rhetorical vision that is communicated to its audience. This study concludes that Hirayamanawari is a complex text composed of various messages and ideologies that go beyond the value focus of each episode. The analysis give insights on the meanings of the text and on the perception of the producers of their target audience, the children.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Hirayamanawari -- Filipino children's stories